Answer: 405 yd squared
Step-by-step explanation:
V = (bh)/2
b = (15 x 9)/2 = 67.5
67.5 x 12 = 810
810/ 2 = 405
ANSWER
See below
EXPLANATION
Given
![f(x) = \frac{ {x}- 9 }{x + 5}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B%20%7Bx%7D-%209%20%7D%7Bx%20%2B%205%7D%20)
and
![g(x) = \frac{ - 5x - 9}{x - 1}](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%20%20%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20)
![(f \circ \: g)(x)= \frac{ (\frac{ - 5x - 9}{x - 1})- 9 }{(\frac{ - 5x - 9}{x - 1} )+ 5}](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%29-%209%20%7D%7B%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20%29%2B%205%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9(x - 1)}{x - 1}}{\frac{ - 5x - 9 + 5(x - 1)}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209%28x%20-%201%29%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205%28x%20-%201%29%7D%7Bx%20-%201%7D%20%7D%20)
Expand:
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9x + 9}{x - 1}}{\frac{ - 5x - 9 + 5x - 5}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209x%20%20%2B%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205x%20-%205%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9x + 9 - 9}{x - 1}}{\frac{ - 5x + 5x - 5 - 9}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209x%20%20%2B%209%20-%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20%2B%205x%20-%205%20-%209%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 14x }{x - 1}}{\frac{ -14}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%2014x%20%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-14%7D%7Bx%20-%201%7D%20%7D%20)
Since the denominators are the same, they will cancel out,
![(f \circ \: g)(x)= \frac{ - 14x}{ - 14} = x](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%5Cfrac%7B%20-%2014x%7D%7B%20-%2014%7D%20%20%3D%20x)
Answer:
Step-by-step explanation:
non linear because linear has always to the first power
7.0267
Step-by-step explanation:
The clue here is that the decimal point follows after the "and"
For example,
One and one thousandth = 1 + 1/1000 = 1.001
One and two hundred sixty-three thousandths = 1+ 263/1000 = 1.263
Hence;
seven and two hundred sixty-seven ten thousandths= 7+ 267/10000= 7.0267
Learn More
Decimal points form :brainly.com/question/232702
Keywords : hundred, ten thousandths,decimal
#LearnwithBrainly
Answer:
Final answer is
and
.
Step-by-step explanation:
Given equation is
.
Now we need to solve that by factoring.
![9x^2+24x+20=4](https://tex.z-dn.net/?f=9x%5E2%2B24x%2B20%3D4)
![9x^2+24x+20-4=0](https://tex.z-dn.net/?f=9x%5E2%2B24x%2B20-4%3D0)
![9x^2+24x+16=0](https://tex.z-dn.net/?f=9x%5E2%2B24x%2B16%3D0)
![9x^2+12x+12x+16=0](https://tex.z-dn.net/?f=9x%5E2%2B12x%2B12x%2B16%3D0)
![3x(3x+4)+4(3x+4)=0](https://tex.z-dn.net/?f=3x%283x%2B4%29%2B4%283x%2B4%29%3D0)
![(3x+4)(3x+4)=0](https://tex.z-dn.net/?f=%283x%2B4%29%283x%2B4%29%3D0)
, ![(3x+4)=0](https://tex.z-dn.net/?f=%283x%2B4%29%3D0)
, ![3x+4=0](https://tex.z-dn.net/?f=3x%2B4%3D0)
, ![3x=-4](https://tex.z-dn.net/?f=3x%3D-4)
, ![x=-\frac{4}{3}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B4%7D%7B3%7D)
Hence final answer is
and
.